Children affected with HIV/AIDS: Information of HIV/AIDS in five Colombian cities* (Colombia Medica, 2011)
Objectives: To describe information about HIV/AIDS in a youth population under 18 years of age affected with HIV/AIDS and caregivers in five Colombian cities: Cali, Buenaventura, Barranquilla, Santa Marta, and Cartagena. Methods: 286 personal surveys were conducted: 11 of children who were aware of their status of involvement with HIV/AIDS and 275 of caregivers of children who did not know their status of involvement with HIV/AIDS. The surveys were conducted in health institutions in the State and private sectors and private, using instruments in line with training programs from participating institutions to inquire about HIV/AIDS. Descriptive analysis was performed of the data and tabulation was done with the SPSS program. Results: Most children who knew their status of involvement with HIV/AIDS report that by acquiring the HIV virus, they may develop other diseases; however, half of these fail to recognize that AIDS weakens the body’s ability to fight infection. The children surveyed partly recognized the HIV/AIDS transmission and treatment mechanisms, while caregivers possess adequate information on the disease. We found reasons to delay the delivery of diagnosis by caregivers 96.2% (N=275) related to avoiding psychological harm to the children, and that if they were to know said status, they might inadvertently disclose this to others, probably exposing them to stigma and/or discrimination. Likewise, professionals providing health services to HIV seropositive children express lack of training regarding the proper procedure and age to reveal such information. Conclusions: It is a priority to enhance the capacity, information, and education of patients about effects, characteristics, manifestations, and treatment of the disease within the comprehensive health management processes conducive to supporting affected families.